Oxidative stress, mitochondrial dysfunction and calcium overload in human lamina cribrosa cells from glaucoma donors. - DOCHERTY, NEIL (My University, 2011)
Oxidative stress is implicit in the pathological changes associated with glaucoma. The purpose of this study was to compare levels of oxidative stress in glial fibrillary acid-negative protein (GFAP) lamina cribrosa (LC) cells obtained from the optic nerve head (ONH) region of 5 normal (NLC) and 4 glaucomatous (GLC) human donor eyes and to also examine mitochondrial function and calcium homeostasis in this region of the ONH. METHODS: Intracellular reactive oxygen species (ROS) production was examined by a thiobarbituric acid reactive substances (TBARS) assay which measures malondialdehyde (MDA), a naturally occurring product of lipid peroxidation and is used as an indicator of oxidative stress. Mitochondrial membrane potential (MMP) and intracellular calcium ([Ca(2+)](i)) levels were evaluated by flow cytometry using the JC-1 (5,5',6,6'-tetrachloro-1,1',3,3'-tetrabenzimidazolecarbocyanine iodide) and fluo-4/AM probes respectively. Anti-oxidant and Ca(2+) transport system gene and protein expression were determined by real time polymerase chain reaction (RT-PCR) using gene-specific primer/probe sets and western immunoblotting, respectively. RESULTS: Intracellular ROS production was increased in GLC compared to NLC (27.19 ± 7.05 µM MDA versus 14.59 ± 0.82 µM MDA, p < 0.05). Expression of the anti-oxidants Aldo-keto reductase family 1 member C1 (AKR1C1) and Glutamate cysteine ligase catalytic subunit (GCLC) were significantly lower in GLC (p = 0.02) compared to NLC control. MMP was lower in GLC (57.5 ± 6.8%) compared to NLC (41.8 ± 5.3%). [Ca(2+)](i) levels were found to be higher (p < 0.001) in GLC cells compared to NLC. Expression of the plasma membrane Ca(2+)/ATPase (PMCA) and the sodium-calcium (NCX) exchangers were lower, while intracellular sarco-endoplasmic reticulum Ca(2+)/ATPase 3 (SERCA) expression was significantly higher in GLC compared to NLC. Subjection of NLC cells to oxidative stress (200 µM H(2)0(2)) reduced expression of Na(+)/Ca2(+) exchanger 1 (NCX 1), plasma membrane Ca2+ ATPase 1 (PMCA 1), and PMCA 4 as determined by RT-PCR. CONCLUSIONS: Our data finds evidence of oxidative stress, mitochondrial dysfunction and impaired calcium extrusion in GLC cells compared to NLC cells and suggests their importance in the pathological changes occurring at the ONH in glaucoma. Future therapies may target reducing oxidative stress and / or [Ca(2+)](i).
PUBLISHED
Keywords: Psychiatry